‘MATHUB’: Development and Usability Evaluation of an Interactive App for Learning Number Patterns in Middle School - Pradana, Kenny Candra; Noer, Sri Hastuti; Sutiarso, Sugeng (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2025)
This study aimed to develop and evaluate “MatHub,” an Android-based interactive multimedia application designed to support students' understanding of number patterns in middle school mathematics. The research followed the ADDIE model, comprising analysis, design, development, implementation, and evaluation stages. The participants included eighth-grade students and a mathematics teacher from SMP Negeri 4 Bandar Lampung. Data were collected through observations, interviews, and questionnaires. The application was validated by media and content experts, who confirmed its strong visual and linguistic feasibility, as well as the relevance and clarity of its content. Student and teacher feedback highlighted that MatHub featured engaging visuals, user-friendly navigation, and accessible language, which enhanced motivation and comprehension. Revisions were made based on suggestions, particularly to improve multimedia elements. Despite facing limitations related to application size and device compatibility, the product was successfully implemented and received positively. These findings suggest that MatHub is a valid and practical learning tool that can enrich classroom experiences and is recommended for broader application in mathematics education at the junior high school level.